Faktor-Faktor yang Mempengaruhi Permintaan Konsumen Teh Raja - Laila Ayu Rafika; Sri Astuti; Camelia Safitri (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2023)
Utilization of technological advances makes ready-to-drink tea drinks a lifestyle of various groups of people who like instant and fast food and beverage products so that they can support their daily activities, that's why ready-to-drink tea products have sprung up offering many advantages and different flavors. latest. The researcher aims to describe the factors of consumer demand for Teh Raja products, namely ready-to-eat tea which continues to grow, in order to get a good response from the community so that the product survives. This study uses descriptive qualitative research. The data collection techniques carried out in this study are active participatory observation, semi-structured interviews, and documentation, the validation of the data used is done by triangulation. Teh Raja is moderate consumer income and consumer tastes in Teh Raja products are satisfied because the taste of Teh Raja is in accordance with the tastes of local consumers and feels satisfied.